Community Service Efforts to Strengthen Indonesian Cultural Literacy Based on Virtual Box Reality for Deaf Children - Rahayu, Sri; Rahayu, Poppy Sonia; Fajruddin Syauqi, Ahmad; Lestari, Ni Made Wida; Ahmad, Ahmad; Hardika, Hardika; Desyanty, Ellyn Sugeng (Universitas Negeri Padang, 2024)
The problem with SLB-B Sumber Dharma Malang is the low knowledge of grade 4 and 5 students regarding Indonesian cultural literacy. This is because the learning media applied by teachers is only through YouTube, so the delivery of Indonesian cultural literacy material is less than optimal. The program aims to strengthen Indonesian cultural literacy for deaf students at SLB-B Sumber Dharma Malang with learning media based on Virtual Box Reality and the Lidantara application. The program implementation method consists of preparation, implementation, closing, evaluation and drawing conclusions. Based on the pre-test, post-test and sharing session, the results showed that the implementation of the Lidantara’s program had an impact on increasing the percentage of students' knowledge and understanding regarding Indonesian cultural literacy from 47% to 97%, and students were able to retell the cultural content they had seen in a coherent manner, clear and comprehensive. Thus, the results of the Lidantara’s program have been proven to be able to overcome partner problems. The sustainability of the program is by forming a team of teachers and students and guaranteeing by including the Lidantara’s program in the school's additional curriculum. Keywords: Indonesian cultural literacy, Virtual Box Reality, Devotion